Exploration Into The Ability of Fifth-Grade Students to Solve Decimal Problems Using Proportional Reasoning - Dwi Ambarwati; Masduki Masduki (Perspektif Ilmu Pendidikan, 2024)
Proportional Reasoning is a complex mathematical way of thinking about interconnected ideas such as multiplication and division of whole numbers, fractions, ratios, powers, measurements, and percent. This research aims to identify students' thinking processes in solving decimal problems that require proportional reasoning. This research was conducted on 5th grade elementary school students in Klaten, Central Java, Indonesia, using test instruments, interviews and documentation studies. The test given consists of five types of questions, namely tests on questions that require students to use additive, multiplicative thinking skills, use reasonable or appropriate ratios, build unit structures (groupings), and understand invariants. The research results found that the proportional reasoning indicator that was more dominantly used by students was the ability to think multiplicatively, while the sub-indicators were writing and completing calculations but the final results were not correct. Apart from that, other findings explain that the low ability is due to the prerequisite material not being mastered, students not understanding the questions, and students not understanding the concept of the topic. Thus, these results confirm that proportional reasoning abilities in grade 5 elementary school are still quite low.